High strength W/TiNi micro-laminated composite with transformation-mediated ductility. (15th September 2016) - Shao, Yang; Yu, Kaiyuan; Jiang, Daqiang; Yu, Cun; Ren, Yang; Jiang, Xiaohua; Guo, Fangmin; Cui, Lishan
Abstract: A laminated W/TiNi composite is fabricated by hot pressing under vacuum and subsequent forging. The W and TiNi constituents are about 250 μm and 80 μm respectively in thicknesses and their interfaces are chemically sharp with negligible intermixing. The material exhibits two yielding plateaus and excellent strength-ductility combination during compression tests. In situ X-ray technique is employed to demonstrate that the unusual yielding phenomenon is related to the reversible thermoelastic phase transformation of TiNi layers. Such mechanisms also contribute to the damage tolerance of the materials by inhibiting crack propagation in W. Graphical abstract: Highlights: A novel W/TiNi micro-laminated composite has been successfully fabricated. The W/TiNi micro-laminated composite exhibits superior mechanical property. The transformation induced plasticity plays an important role in compression. The composite exhibits high damage tolerance due to the crack deflection and the bridging effect.